Analisis Kepuasan Pasien Peserta BPJS Pada Instalasi Rawat Jalan Poliklinik Bedah Rumah Sakit Umum Pusat Dr. M. Djamil Padang - Yolandafitri Zulvia; Indry Putri Yulisa (Universitas Negeri Padang, 2020)
This study aims to determine the patient satisfaction of BPJS participants based on five dimensions, namely, tangible, reliability, responsiveness, assurance, and empathy. This research method uses descriptive research methods. The author collects data directly through a questionnaire. The sample in this study were 100 respondents (BPJS participants in the Outpatient Installation of Surgical Polyclinic at M Djamil Hospital). Samples are taken using the Slovin formula, which is a formula for calculating the minimum number of samples. Data collection methods used are field studies (distributing questionnaires and observations). Based on the results obtained, the author can provide a conclusion that the satisfaction of BPJS participants in the Outpatient Installation of the Surgical Polyclinic at RSUP M Djamil Padang has been quite satisfied. Although there are still a number of things that are not optimal, it is expected that at RSUP M Djamil Padang to provide maximum satisfaction to BPJS participants